Uncle John [videorecording (DVD)] - Piet, Steven; Ashton, John, 1948-; Moffat, Alex; Lyng, Jenna (Kino Lorber, 2016)
In this tale of small town intrigue, an urbanite returns to his quiet hometown on an impromptu trip as his Uncle, widely respected in town, struggles to evade suspicion of a murder.